Peningkatan Daya Tarik Wisata Kuliner Kota Cirebon melalui Kualitas Pelayanan dan Kualitas Produk : (Studi Kasus: Empal Gentong Bu Dharma Jalan Diponogoro) - Iva Yulia Mustafa; Fitriatunissa Shabrina (Jurnal of Management and Social Sciences, 2024)
Empal Gentong Bu Dharma Jalan Diponogoro is not just a dish, but is also a symbol of Cirebon's culinary tradition which is rich in spices and distinctive flavors. Its presence not only satisfies the taste buds, but also carries a valuable cultural heritage from generation to generation. However, behind the reputation that has been built, new challenges have emerged amidst the ever-changing dynamics of the culinary industry. This research aims to investigate the strategies and efforts that can be carried out by Empal Gentong Bu Dharma Jalan Diponogoro in increasing the attractiveness of Cirebon City culinary tourism through improving the quality of its services and products. An in-depth case study at Empal Gentong Bu Dharma Jalan Diponogoro will provide a deeper understanding of the challenges and opportunities faced by culinary entrepreneurs in Cirebon City. The research method used in this research is a combination method or mixed methods, this method is a combination of qualitative and quantitative methods.